Penerapan Kelompok Masyarakat Peduli Pemasyarakatan (POKMAS LIPAS) Dalam Proses Pembimbingan Klien Pemasyarakatan Balai Pemasyarakatan Kelas II Pangkal Pinang - Nata Mulia Hammami; Umar Anwar (Jurnal Pendidikan dan Konseling (JPDK), 2023)
The Correctional System in order to form Penitentiary Assisted Citizens (WBP) to become whole human beings, aware of mistakes, improve themselves, and not repeat criminal acts, can be accepted again by the community, play an active role in development, and live normally as a good and responsible society need preparation for correctional inmates. The correctional center, hereinafter referred to as the father, is an institution or place that carries out the function of community guidance for clients. This study aims to describe the implementation of coaching carried out by many people involving the community. POKMAS LIPAS is a community group that collaborates with Correctional Centers which was formed because of community concern for the goals of the correctional system. In line with the aim of optimizing Lipas Pokmas, this can be done to support the process that Correctional Clients are still carrying out in preparing themselves to return to society as whole human beings. Keyword : Correctional System, Balai Pemasayarakatan, POKMAS LIPAS, Correctional Client